Decision to Choose Acupuncture Therapy for Degenerative Diseases among the Elderly at Ja’far Medika Hospital, Karanganyar - Purwanto -; Ruben Dharmawan; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Aging process results in biological, physical, and mental changes in the elderly. Degenerative diseases are common in the elderly. They can be treated by pharmacologic or non pharmacologic treatment. Acupuncture therapy potentially can be used as a complementary or alternative therapy to treat degenerative diseases in the elderly. This study aimed to investigate factors that determine the decision to choose acupuncture therapy for the degenerative diseases in the elderly at Ja’far Medika Hospital, Karanganyar, Central Java.SubjectsandMethod: This was a qualitative study with phenomenology approach. This study was conducted at Ja’far Medika Hospital, Karanganyar, Central Java, fromMarch to April 2015. Ten informants were selected for this study by purposive sampling. The data were collected by in-depth interview, observation, and document review.They were validated by source triangulation, and analyzed by Miles and Huberman method.Results: The sample consisted of 5 men and 5 women, aged 53 to 72 years old, with school attainment varying from primary school to university graduate. Job category included farmer, civil servant, and pensioner. The degenerative diseases that were treated by acupuncture therapy including post-stroke, hernia nucleous pulposus, and eyelid disorder. Internal factors that determined the decision to choose acupuncture were motivation to recover, (religious) belief, and boredom to medical service. External factors that determined the decision to choose acupuncture included the quality of service, family support, trust in the therapist, and hospital image. According to the informants, the acupuncture therapy could help recover their health from the degenerative diseases. Most of them used acupuncture as a complementary treatment.Conclusion: Some internal and external factors determine the decision to choose acupuncture therapy for the degenerative health problem in the elderly. Acupuncture treatment is reported to help recover health in the elderly. Keywords: acupuncture, decision, degenerative disease, elderlyCorrespondence: Purwanto. Masters Program in Public Health, Sebelas Maret University. Email: Purwanto.akp@gmail.com. Mobile: 081393289784.Journal of Health Promotion and Behavior (2016), 1(2): 127-137https://doi.org/10.26911/thejhpb.2016.01.02.08